RISE: Addressing public health concerns through university-industry collaboration / Dr Nurdiana Samsulrizal - Samsulrizal, Nurdiana (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
Bio Fluid Sdn Bhd, a local manufacturer of high-quality and effective healthcare products has signed a Memorandum of Understanding (MoU) with Universiti Teknologi MARA on 28 December 2020.